2014
DOI: 10.1007/s10096-014-2245-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL7RA polymorphisms and the successful therapy against HCV in HIV/HCV-coinfected patients

Abstract: Interleukin-7 (IL-7) is a critical factor in maintaining or inducing effective antiviral CD4+ and CD8+ T-cell responses. The aim of this study was to examine the association of interleukin-7 receptor-α (IL7RA) polymorphisms with a sustained virologic response (SVR) after hepatitis C virus (HCV) therapy with pegylated interferon-alpha plus ribavirin (pegIFNα/ribavirin) in 177 human immunodeficiency virus (HIV)/HCV-coinfected patients. We performed a retrospective study in 177 naïve patients who started HCV trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…There is a considerable controversy about adjusting the “p value” after multiple tests on clinical-orientated studies [ 48 , 49 ]. In our study there was a hypothesis supported by theory and previous reports in several infectious diseases [ 10 , 11 ], including HIV infected subjects [ 13 , 14 ] and HIV/HCV coinfected patients [ 15 ], and showing a key role of IL7R polymorphisms in the evolution of patients. Therefore, we were not literally doing a random search of a meaningful result, and our results should not be affected by the fact of carrying out a high number of statistical tests.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There is a considerable controversy about adjusting the “p value” after multiple tests on clinical-orientated studies [ 48 , 49 ]. In our study there was a hypothesis supported by theory and previous reports in several infectious diseases [ 10 , 11 ], including HIV infected subjects [ 13 , 14 ] and HIV/HCV coinfected patients [ 15 ], and showing a key role of IL7R polymorphisms in the evolution of patients. Therefore, we were not literally doing a random search of a meaningful result, and our results should not be affected by the fact of carrying out a high number of statistical tests.…”
Section: Discussionsupporting
confidence: 89%
“…However, OR values were similar to those obtained for individual SNPs. In this regard, we also recently reported that IL7R CTA haplotype (three alleles associated with higher sCD127 levels) was related to lower odds of achieving a SVR [ 15 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, IL7RA polymorphisms are related to autoimmune diseases [ 22 , 23 ] and CD4+ T cell recovery in human immunodeficiency virus (HIV)-infected patients on antiretroviral therapy [ 24 26 ]. Among HCV-infected patients, IL7RA polymorphisms have been associated with the response to peg-interferon (IFN)-α/ribavirin therapy against HCV and severe liver fibrosis in HIV/HCV-coinfected patients [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%